COUNTING RATIONAL POINTS ON A CERTAIN EXPONENTIAL-ALGEBRAIC SURFACE - Pila, J (2010)
We study the distribution of rational points on a certain exponential-algebraic surface and we prove, for this surface, a conjecture of A. J. Wilkie.